Mullen Scales of Early Learning Adaptation for Assessment of Indian Children and Application to Tuberculous Meningitis. (4th July 2020) - Nimkar, Smita; Joshi, Suvarna; Kinikar, Aarti; Valvi, Chhaya; Devaleenal, D Bella; Thakur, Kiran; Bendre, Manjushree; Khwaja, Saltanat; Ithape, Mahesh; Kattagoni, Krishna; Paradkar, Mandar; Gupte, Nikhil; et al.
Abstract: Introduction: Tuberculous meningitis (TBM) results in significant morbidity and mortality among children worldwide. Associated neurocognitive complications are common but not well characterized. The Mullen Scales of Early Learning (MSEL), a well-established measure for assessment of neurodevelopment, has not yet been adapted for use in India. This study's goal was to adapt the MSEL for local language and culture to assess neurocognition among children in India, and apply the adapted measure for assessment of children with TBM. Methods: Administration of MSEL domains was culturally adapted. Robust translation procedures for instructions took place for three local languages: Marathi, Hindi and Tamil. Multilingual staff compared instructions against the original version for accuracy. The MSEL stimuli and instructions were reviewed by psychologists and pediatricians in India to identify items concerning for cultural bias. Results: MSEL stimuli unfamiliar to children in this setting were identified and modified within Visual Reception, Fine-Motor, Receptive Language and Expressive Language Scales. Item category was maintained for adaptations of items visually or linguistically different from those observed in daily life. Adjusted items were administered to six typically developing children to determine modification utility. Two children diagnosed with confirmed TBM (ages 11 and 29 months) were evaluated with the adapted MSEL before receiving study medications. Skills were below age-expectation across visual reception, fine motor and expressive language domains. Conclusions: This is the first study to assess children with TBM using the MSEL adapted for use in India. Future studies in larger groups of Indian children are warranted to validate the adapted measure.